Morphology, crystalline structure and chemical composition of MAO treated Ti-15Zr-Mo surfaces enriched with bioactive ions - Sousa, Tiago Santos Pereira [UNESP] (2019)
In this study, MAO treatment was used to enrich, with bioactive Ca, Mg and P atoms, as-casted and heat-treated Ti-15Zr-xMo (x = 0, 5, 10 and 15 wt%) alloys, for potential use as advanced metallic biomaterials. The chemical composition of the surface was evaluated by EDS and XPS measurements. The morphology and microstructure was analyzed by OM and SEM images. Crystalline structure and phase composition were characterized by XRD measurements. The results indicated that the oxide layers were porous, with microstructural features of the bulk (grain size and secondary phases) slightly affecting the surface characteristics (pore size, chemical and phase composition). The crystalline structure of the oxide layers were composed by a mixture of anatase and rutile phases (TiO2), with a minority of tetragonal zirconia (ZrO2) and traces of CaCO3 and P2O3 compounds. Chemical analysis indicated that the oxide layers were composed mainly by Ti and Zr oxides, with successful incorporation of the bioactive elements. The obtained results evidenced that the surface characteristics of MAO-treated Ti surfaces can be properly adjusted by the addition of alloying elements and implementation of specifc heat treatments on the substrate. This fnding can be quite useful for the development of novel biomedical implants.